(untitled)
Let ? be a non zero complex number. An operator A is a rank one ? *-commutes with B if AB - ? BA* has rank one. If, moreover, B is compact operator then A is called to belong to (H). In other words,(H) = fA 2 B(H)jAB-? BA* has rank one for some compact operator B